2014
DOI: 10.1057/iga.2014.15
|View full text |Cite
|
Sign up to set email alerts
|

In defense of the lowly scorecard: What legislator ratings can tell us about interest groups

Abstract: Oh, the lowly interest group scorecard. Although it has fallen from favor with political scientists in recent decades, we contend scorecards still offer considerable potential for those engaged in interest group research. By aggregating scores across sectors of interests, we can determine under what conditions different types of groups are satisfied with Congress. In our analysis, we aggregate 105 893 ratings of US senators issued by 249 different organizations from the 106th through the 111th Congresses. By '… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 82 publications
(121 reference statements)
0
1
0
Order By: Relevance
“…Scholars have also largely presumed that money and membership are related to policy success (e.g., Berry, 1997:234; Key, :503). Yet, recent studies have found no relationship between organizational wealth or membership and successful policy advocacy (Baumgartner et al., 2009; Berry and Arons, :122–34; Chand, Schreckhise, and Parry, ).…”
Section: Lobbying and Mobilizationmentioning
confidence: 99%
“…Scholars have also largely presumed that money and membership are related to policy success (e.g., Berry, 1997:234; Key, :503). Yet, recent studies have found no relationship between organizational wealth or membership and successful policy advocacy (Baumgartner et al., 2009; Berry and Arons, :122–34; Chand, Schreckhise, and Parry, ).…”
Section: Lobbying and Mobilizationmentioning
confidence: 99%